Public low-cost housing design: the residents' perception - Bashari, Sunusi; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The purpose of this paper is to explore the design of public low-cost housing in Jigawa State, Nigeria and assess how residents perceived the housing units in relation to their culture and impact on their well-being. The housing units were constructed as an intervention by the government for low-income earners. This research was conducted through both qualitative and quantitative approaches. In qualitative aspect, three respondents were interviewed to express their perception on the public low-cost housing design, while quantitative aspect assessed the residential housing attributes of low-cost housing estates with view to identify the important housing attributes considered by the residents for their well-being and was used to support the qualitative aspect. This was achieved through descriptive statistics using Relative Importance Index (RII). A well-structured questionnaire was administered to the residents of public low-cost housing of Jigawa state, Nigeria. The results indicated that, the design of public low-cost housing in Jigawa State, Nigeria does not reflect the culture of the residents, most of the residents were not satisfied with it. In addition, out of fifty five (55) constructs from five (5) housing-related dimensions, the result identified thirty two (32) important attributes out of these, the residents considered twelve (12) to be the most important attributes affecting their well-being. Thus, the paper would serve as a blueprinted government, housing policy makers and housing developers to understand that, the housing constructions and infrastructural elements should reflect the cultural background of the beneficiaries. Views of beneficiaries before and after construction of public low-cost housing are of great importance. The findings of this paper were based on reviewed of earlier studies on residential-housing units, field work and research conducted on particularly the public low-cost housing in Jigawa State, Nigeria.